Analisis Komparasi Kinerja Keuangan Sebelum dan Selama Pandemi Covid-19 pada Perusahaan Sektor E-Commerce yang Terdaftar pada Bursa Efek Indonesia Periode 2019-2020 - Muhammad Nur Kalidasa; Reni Oktavia; Ade Widiyanti; Niken Kusumawardani (Departement of Mathematics Education, 2024)
The purpose of this study is to identify and analyze any differences in financial ratios e-commerce companies which is listed on the Indonesian Stock Exchange (IDX) before and during the Covid-19 pandemic in the period of 2019-2020. The ratios being used are Return On Asset (ROA), Current Ratio (CR) and Debt to Asset Ratio (DAR). The population is technology companies listed on the Indonesian Stock Exchange (IDX) index in the period of 2019-2020. Using purposive sampling, 22 companies were selected as the sample. Paired sample t-test and Wilcoxon signed rank test, which were used previously in normality test, were incorporated. This study did not found differences in Return On Asset (ROA), Current Ratio (CR) and Debt to Asset Ratio(DAR).